Compliance to antihypertensive therapies among outpatients in a hypertension clinic - Chua, Siew Siang; Lee, Y.K.; Chua, C.T.; Abdullah, M.S. (Faculty of Medicine, University of Malaya, 2002)
Many studies have shown that failure in the conlTol of hypertension with oral antjhypertensivescould be associated with noncompliance. The present study was conducted to assess the compliance rate to antihypertensive therapies and also to detennine factors related to any noncompliance. The study was conducted in a leaching hospital in Kuala Lumpur. Data was collected from patients' medical re<:ords and via personal interview using a structured questionnaire. Out of a total of175 respondents recruited in the study, 49.1% missed alleast a dose of their antihypertensive agents during a one'month period. The most common reason given by respondents who were not compliant to their antihypertensive therapies was forgetfulness (91.8%), followed by too busy (20.0%) and insufficient medication supplied to them (18.8%). None of the factors analysed, including the demography of the respondents, their knowledge about hypertension and the types of antihypertensive therapies they were on, had any statistically significant influence on the compliance behaviour of the respondents to their anti.hypertensive therapies. However, more than 80% of the respondents kept their appointment to see their doctor and only this factor appeared to be related to the medication compliance behaviour although it still did not reach any statistical significance.